2021
DOI: 10.1186/s12870-021-03321-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel QTL contributing to barley yellow mosaic resistance in wild barley (Hordeum vulgare spp. spontaneum)

Abstract: Background Barley yellow mosaic disease (BYMD) caused by Barley yellow mosaic virus (BaYMV) and Barley mild mosaic virus (BaMMV) seriously threatens the production of winter barley. Cultivating and promoting varieties that carry disease-resistant genes is one of the most powerful ways to minimize the disease’s effect on yield. However, as the BYMD virus mutates rapidly, resistance conferred by the two cloned R genes to the virus had been overcome by new virus strains. There is an urgent need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Rph15 is a gene derived from wild barley conferring resistance to leaf rust (Chen et al 2021). A novel QTL qRYM-2Ha contributing to barley yellow mosaic resistance was identified in wild barley (Pan et al 2021). Association and expression analysis revealed that Tibetan wild barley offers elite alleles of HvHKT1 and HvHKT2 conferring salinity tolerance (Qiu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rph15 is a gene derived from wild barley conferring resistance to leaf rust (Chen et al 2021). A novel QTL qRYM-2Ha contributing to barley yellow mosaic resistance was identified in wild barley (Pan et al 2021). Association and expression analysis revealed that Tibetan wild barley offers elite alleles of HvHKT1 and HvHKT2 conferring salinity tolerance (Qiu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rph15 is a gene derived from wild barley conferring resistance to leaf rust (Chen et al 2021). A novel QTL qRYM-2Ha contributing to barley yellow mosaic resistance was identi ed in wild barley (Pan et al 2021). Association and expression analysis revealed that Tibetan wild barley offers elite alleles of HvHKT1 and HvHKT2 conferring salinity tolerance (Qiu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Severity scores of 0 to 4 represent the damage caused by virus infection from light to severe ( Fig. 1 ): 0 means healthy leaves with no symptoms of disease, 1 represents typical chlorotic spots, 2 indicates a quarter of the leaves display a yellow mosaic pattern, 3 represents more than half of the leaves display a yellow mosaic pattern, and 4 indicates more than three-quarters of the leaves display yellow mosaic pattern ( Pan et al, 2021 ). Afterwards, a standardized area under the disease progress steps (sAUDPS) index was used for the evaluation of disease resistance, which can effectively combine and transform multiple investigations of disease grades into a single value for further GWAS analysis ( Simko & Piepho, 2012 ).…”
Section: Methodsmentioning
confidence: 99%